2021
DOI: 10.1111/tmi.13539
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis and meningitis in Western Africa: a scoping review of pathogens

Abstract: Objective To give an overview of the recently reported literature on the aetiologies of meningitis and encephalitis in western sub‐Saharan Africa. Methods We conducted a scoping review following PRISMA guidance on published meningitis and encephalitis cases in the 16 countries of the United Nations‐defined western sub‐Saharan African region as identified in cohort studies, case series, and case reports, published 01/01/2000–08/01/2020, and available in four databases in August 2020 with an abstract in English,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…To date, there is very little data on the etiology of encephalitis in Senegal and more broadly in Sub-Saharan Africa, and the real burden of viral-associated encephalitis is almost unknown. A review of pathogens detected in patients with encephalitis and meningitis in Western Africa showed that most of the studies focused on meningitis, and thus reported mostly bacterial infection [ 20 ]. Less than 0.1% of total cases from 139 published studies were identified as viral encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is very little data on the etiology of encephalitis in Senegal and more broadly in Sub-Saharan Africa, and the real burden of viral-associated encephalitis is almost unknown. A review of pathogens detected in patients with encephalitis and meningitis in Western Africa showed that most of the studies focused on meningitis, and thus reported mostly bacterial infection [ 20 ]. Less than 0.1% of total cases from 139 published studies were identified as viral encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although not all cases of encephalitis have an infectious aetiology, infectious encephalitis accounts for most cases recorded in the tropics [ 4 ]. Viruses constitute the major aetiology for encephalitis and molecular diagnostic techniques such as Polymerase Chain Reaction (PCR) and genome sequencing are the preferred diagnostic techniques for confirmation of viral aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no such comprehensive report is available on encephalitis in West Africa or Africa as a whole. Infectious pathogens of the central nervous system in this region are only known through sporadic case reports [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Although its diagnosis and treatment have improved, encephalitis continues to cause 5.6-39.3% of deaths in affected patients according to reports from different countries. [2][3][4] Even survivors of severe encephalitis suffer from sequelae, such as fatigue, irritability, attention deficit, seizures, memory loss, hearing and vision impairment.…”
Section: Introductionmentioning
confidence: 99%